Who are we protecting? Exploring counsellors’ understanding and experience of boundaries. - Blundell, Peter; Oakley, Lisa; Kinmond, Kathryn (European Journal for Qualitative Research in Psychotherapy, 2022)
The concept of boundaries is a term often used within counselling and psychotherapy literature. However, there is a paucity of research into how useful and meaningful it is as a concept, for counselling and psychotherapy practice. This study researched how counsellors understand and experience boundaries within their counselling practice.  Seven participants, who were all qualified and practicing counsellors, were interviewed about their understanding and experience of boundaries. These interviews were transcribed and then analysed using Interpretative Phenomenological Analysis (IPA). Analysis identified two superordinate themes: Protection and Safety; and The Structure of Therapy. This paper explores the first superordinate theme, which is further divided into two subordinate themes, which are: Protection of Self and Protection of Other. Findings indicate that there was a lack of awareness around boundaries, with some participants describing defensive responses to some boundary issues. However, participants also described using boundaries to restrict, limit and defend themselves when working with clients, and they identified this as necessary for their own safety and security.  This study recommends that therapists should engage reflexively with boundaries within their practice, to ensure practice is client focused.